Quality assurance of clinched joints using explainable machine learning - Gerritzen, Johannes; Chopra, Kunal; Reschke, Gregor; Hornig, Andreas; Brosius, Alexander; Gude, Maik (Journal of Advanced Joining Processes)

Modelling strategies for non-rotationally symmetric joints - Devulapally, Deekshith Reddy; Tröster, Thomas (Materials Research Proceedings)
Abstract. Accurate Finite Element Modeling (FEM) of joints is essential in the design of complex mechanical systems such as automotive body-in-white (BIW) structures, as it plays a critical role in evaluating their performance. Although well-established techniques exist for modeling rotationally symmetric joints, there remains a significant gap in effectively modeling non-rotationally symmetric joints. These joints are particularly relevant in the automotive BIW, where they can better accommodate anisotropic loading conditions. In this study, strategies for modeling non-rotationally symmetric joints were explored using finite element simulations in LS-DYNA. The findings demonstrate that discrete beam elements can capture the anisotropic characteristics of such joints. Two models were tested: a single-beam model for stiffness periodicity every 90°, and a three-beam model for stiffness periodicity every 120°. Force responses, stress distribution, and sheet bending behaviors were analyzed, confirming that discrete beam elements can accurately represent direction-dependent stiffness. These results establish a foundation for developing advanced joint modeling strategies in complex mechanical systems.

Intrinsic Motivation in Stem Outreach: An Analysis of External Factors in Voluntary and School-Based Lab Settings - Reckmann, Eileen; Temmen, Katrin (EDULEARN Proceedings)

Introduction of electronic lab notebooks in engineering education - opportunities for a cultural change - Müller, Laura; Meihöfener, Niclas; Siemoneit, Johannes Gabriel; Mozgova, Iryna (Engineering Education for Sustainable Development (EESD2025))

SMEs within a Data-Driven Sustainable Finance Framework: A European Survey - Rossmann, Felix; Greitens, Jan; Knoll, Lisa

Technik im Fokus: Eine qualitative Analyse kindlicher Themenwünsche in der non-formalen MINT-Bildung - Reckmann, Eileen; Temmen, Katrin

Multilevel fault diagnostics for railway applications using limited historical data - Aimiyekagbon, Osarenren Kennedy; Löwen, Alexander; Hanselle, Raphael; Rief, Thomas; Beck, Maximilian; Sextro, Walter (PHM Society Asia-Pacific Conference)
This study proposes a fault diagnostics methodology that addresses the challenges posed by highly imbalanced datasets typical of railway applications, where faulty conditions constitute the minority class. Fault diagnostics is performed from the component level upward, considering each sensor’s proximity to its respective critical component. Advanced signal analysis, feature engineering, and automated data-driven model generation techniques were explored to achieve comprehensive diagnostics, such that the model development process accounts for variations in the operating conditions and differing levels of information availability. The proposed methodology is evaluated on datasets from the MONOCAB, for scenarios with limited faulty instances and on the Beijing 2024 IEEE PHM Conference data challenge, which focused on fault diagnostics of railway systems under various fault modes and operating conditions.
Keywords: MONOCAB; Beijing Data Challenge; Diagnostics of railway systems

"Wofür bin ich denn hier, wenn ich nicht in irgendeiner Weise auch helfen kann?" Zur Rolle der Lehrkraft beim selbstständigen Songwriting im Unterricht - Godau, Marc; Barreiro, Julia; Hermann, Katharina; Neuhausen, Timo; Maxelon, Dominik; Weidner, Verena (46. Jahresband des Arbeitskreises Musikpädagogische Forschung/46th Yearbook of the German Association for Research in Music Education)
The article explores the role of teachers in self-directed songwriting in school music based on the informal learning approach. It investigates a didactic design that was implemented in six schools and was empirically researched utilizing si-tuational analysis. Based on tensions, that emerge due to conflicting expectations, it can be shown, that the teacher's role extends beyond the dichotomy of directive instruction versus open facilitation. Instead, it encompasses an interplay of six divergent roles which are discussed in their positions in relation to each other. These considerations enrich the understanding of teaching practices in popular music education, emphasizing the redefinition of teacher-student relationships for song-writing in school music.

Die Rolle institutionalisierter Standards für die Hybridisierung musikalischer Praxen. Zur Soziomaterialität von Songwriting-Producing im Bedroom-Studio - Neuhausen, Timo (46. Jahresband des Arbeitskreises Musikpädagogische Forschung/46th Yearbook of the German Association for Research in Music Education)
The role of institutionalized standards for the hybridization of musical practices. On the socio-materiality of songwriting-producing in the bedroom studio This study examines the socio-materiality of hybrid music practices in bedroom studios, focusing on the interplay between traditional music education institutions and YouTube education. A single case situational analysis reveals how standardized instrumental and music production practices are combined to form a hybrid practice. It shows that traditional music education institutions, such as music schools and conservatories, specialize in the selection of chord tones, while You-Tube videos focus on sound design. Using an actor-network theory approach, the study demonstrates the permeability of informal and institutional learning spaces. The findings suggest that songwriting-producing is not simply a sum of different practices, but rather a process of negotiation and compromise between different standards and goals, as well as the distribution of practice between humans and technology.

Über Rätsel zur Quantenphysik – Eine spielerische Heranführung an ein abstraktes Thema - Ebert, Marc; Temmen, Katrin

Bolted Langevin transducers with leadfree piezoelectric ceramics - Scheidemann, Claus; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias
Lead-containing piezoelectric ceramics are still the base for today’s ultrasonic transducers used in broad applications. This is partly due to missing powerful lead-free piezoelectric ceramic parts in the commercial market. There has been much research on lead-free materials but developing them into marketable parts seems to be an ongoing process. The actual exemption of ROHS has expired, but as the new exemption has already been requested, ceramic suppliers keep on selling lead containing products. Nevertheless, these should be replaced by lead-free alternatives for environmental and health issues. This contribution focuses on exploring the technological readiness level of lead-free hard piezoceramics for prestressed ultrasonic transducers. A small series of bolted Langevin transducers was set up with standard PZT material and three commercial lead-free variants. Results of the building process from individual ring ceramic characteristics to transducer load tests are presented. The main finding of this study is that the lead-free materials technically can compete with the standard PZT for medium-power applications. Some adaptations in the ultrasonic system must be done: the geometry must be altered to fit resonance frequency, and higher voltages or thinner ceramics are needed to achieve the same vibration level at low load. For reaching same power, the volume of lead-free ceramics must be 1.5 to 3 times larger. As already promoted in literature, mechanical losses at high vibration levels are smaller for the lead-free materials. This might help to argument lead-free piezoelectric materials in some applications. References 1. Directive 2011/65/EU of the European Parliament and of the Council of 8 June 2011 on the Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment. EUR-Lex Document 02011L0065-20240801. Available online: http://data.europa.eu/eli/dir/2011/65/2024-08-01 (accessed on 24 January 2025). 2. Langevin, P. (1918) Method and Apparatus for Transmitting and Receiving Submarine Elastic Waves Using the Piezoelectric Properties of Quartz. French Patent Office; Patent No. FR505703. 3. Hemsel, T.; Twiefel, J. (2023) Piezoelectric Ultrasonic Power Transducers. In Encyclopedia of Materials: Electronics; Academic Press: Oxford, UK; pp. 276–285. https://doi.org/10.1016/b978-0-12-819728-8.00047-4. 4. ATHENA Technologie Beratung GmbH (2025) Description of Ultrasound Generator. Available online: http://shop.myathena.de/epages/12074748.sf/de_DE/?ObjectPath=/Shops/12074748/Products/AM200 (accessed on 13 January 2025). 5. Littmann, W.; Hemsel, T.; Kauczor, C.; Wallaschek, J.; Sinha, W. (2003) Load-adaptive phase-controller for resonant driven piezoelectric devices. Proc. World Congr. Ultrason. 2003, 48, 547–550. 6. Scheidemann, C., Bornmann, P., Littmann, W., & Hemsel, T. (2025). Lead-Free Ceramics in Prestressed Ultrasonic Transducers. Actuators, 14(2), 55. https://doi.org/10.3390/act14020055
Keywords: lead free piezoelectric ceramics; bolted Langevin transducer; medium power ultrasound.

Intensive ultrasonic cleaning of surfaces by means of lead-free ultrasonic transducer with focussing sonotrode - Hemsel, Tobias; Scheidemann, Claus; Bornmann, Peter; Littmann, Walter; Sextro, Walter
Intensive ultrasonic cleaning of surfaces by means of a lead-free ultrasonic transducer with focusing sonotrode Ultrasonic cleaning baths are probably a coincidental development: After underwater sonars had already been successfully used to detect submarines before 1920, it was probably observed in this environment that the ultrasonic oscillators not only showed a self-cleaning effect but also cavitation damage. At the beginning of the 1950s, the first ultrasonic cleaning devices finally came onto the market. Today, the range of applications ranges from household appliances for jewellery and eyewear cleaning to classic cleaning baths for metal parts and systems for cleaning highly sensitive electronic components. There is a certain gap in handheld, mobile cleaning equipment. Although devices for spot cleaning of textiles are known, the cleaning effect is usually low. Due to the directive 2011/65/EU on the restriction of the use of hazardous substances in electrical and electronic equipment (RoHS) [1] lead should no longer be used in technical devices. As today’s standard ceramics for medium and high-power ultrasonic transducers typically contain lead, there is a need to explore the use of lead-free ceramics in this field. Honda [2] already offers a cleaning transducer based on lead-free piezoelectric ceramics, but it is designed to be used in cleaning baths. This article presents the model-based development of a highly innovative ultrasonic cleaner. On the one hand, lead-free piezoelectric ceramics are used, and on the other hand, a special sonotrode has been developed that concentrates the sound in such a way that a strong cavitation and thus cleaning effect is achieved with comparatively low power in a short time. Coupled field finite element method was used to find an appropriate geometry for the focussing sonotrode. The comparison of simulation and measurement results shows that the lead-free piezoceramics used do their job well and can keep up with standard ceramics, but more ceramic volume is needed to achieve same power. An advanced control concept was elaborated to ensure continuous hard cavitation at varying distances between the sonotrode and the part to be cleaned. Cleaning results for different surfaces and contaminations are presented. The concept of the focusing sonotrode shows that a convincing cleaning result can be achieved even with low power and in short time, provided that the oscillation system and control electronics are suitably coordinated. References [1] http://data.europa.eu/eli/dir/2011/65/2024-08-01 [2] https://en.honda-el.co.jp/product/ceramics/lineup/lead_off/lead-off

Time dependent material characteristics of prestressed piezoelectric ceramics in langevin transducers - Scheidemann, Claus; Hemsel, Tobias; Sextro, Walter

Investigation of the Setting Behaviour of Mechanically Biased Piezoelectric Ultrasonic Transducers - Scheidemann, Claus; Porzenheim, Julius; Hemsel, Tobias; Sextro, Walter

The impact of AI on engineering design procedures for dynamical systems - de Payrebrune, Kristin M.; Flaßkamp, Kathrin; Ströhla, Tom; Sattel, Thomas; Bestle, Dieter; Röder, Benedict; Eberhard, Peter; Peitz, Sebastian; Stoffel, Marcus; Rutwik, Gulakala; Aditya, Borse; Wohlleben, Meike Claudia; et al. (Technische Mechanik - European Journal of Engineering Mechanics)
Artificial intelligence (AI) is driving transformative changes across numerous fields, revolutionizing conventional processes and creating new opportunities for innovation. The development of mechatronic systems is undergoing a similar transformation. Over the past decade, modeling, simulation, and optimization techniques have become integral to the design process, paving the way for the adoption of AI-based methods. In this paper, we examine the potential for integrating AI into the engineering design process, using the V-model from the VDI guideline 2206, considered the state-of-the-art in product design, as a foundation. We identify and classify AI methods based on their suitability for specific stages within the engineering product design workflow. Furthermore, we present a series of application examples where AI-assisted design has been successfully implemented by the authors. These examples, drawn from research projects within the DFG Priority Program SPP~2353: Daring More Intelligence - Design Assistants in Mechanics and Dynamics, showcase a diverse range of applications across mechanics and mechatronics, including areas such as acoustics and robotics.

Surrogate-Assisted Multi-objective Design of Complex Multibody Systems - Amakor, Augustina C.; Berkemeier, Manuel B.; Wohlleben, Meike Claudia; Sextro, Walter; Peitz, Sebastian (Lecture Notes in Computer Science)

Methodenentwicklung zur numerischen Auslegung von Klebverbindungen mit lackierten Fügeteilen - Hofmann, Julia; Teutenberg, Dominik; Meschut, Gerson (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Optimierung modularer Produkte für die Mobilität: Ein Klassifizierungsrahmen für zirkuläre Produkte - Rohde, Katharina; Ott, Manuel; Budde, Finn Lukas; Mozgova, Iryna (Solving Conflicts on the Way to Sustainable Mobility: Technische und betriebswirtschaftliche Aspekte)
Für die Aufrechterhaltung der natürlichen Ressourcen ist eine effiziente Nutzung dieser essenziell. Vor diesem Hintergrund untersucht das vorliegende Paper die Rolle der Kreislaufwirtschaft als wegweisendes Wirtschaftsmodell, das von der Europäischen Union gefördert wird. Ziel der Kreislaufwirtschaft ist es, den Ressourcenverbrauch und die Abfallproduktion zu minimieren, indem ein kontinuierlicher Kreislauf aus Nutzung, Wiederverwendung und Recycling von Materialien geschaffen wird. Ein zentraler Aspekt dabei ist der Produktentwicklungsprozess (PEP) - ein vielschichtiger Prozess mit zahlreichen Einflussfaktoren und theoretisch unbegrenzten Gestaltungsmöglichkeiten. Diese Vielfalt führt jedoch zu erheblichen Entscheidungsunsicherheiten, die die Umsetzung von Kreislaufwirtschaftsprinzipien erschweren können. Um diese Herausforderungen zu adressieren, wird ein methodischer Prozess vorgestellt, der eine systematische Klassifizierung im Zusammenhang mit umliegenden Bauteilen ermöglicht. Die Methodik basiert auf einer strukturierten Bewertung von Bauteilen hinsichtlich ihrer Relevanz für die Kreislaufwirtschaft. Dabei werden zentrale Aspekte wie Wiederverwendbarkeit, Recyclingfähigkeit und Ressourceneffizienz berücksichtigt, darunter: • Handelt es sich um ein Gebrauchs- oder Verbrauchsprodukt? • Ist das Bauteil eine Wiederverwendung oder eine Neufertigung? • Ist das Bauteil standardisiert, zugekauft oder individuell ausgerichtet? • Welche primäre Funktion nimmt das Bauteil ein? Diese strukturierte Klassifizierung unterstützt die Entscheidungsfindung bereits früh im PEP. Sie ermöglicht es Produktentwickelnden, Potenziale für die Kreislaufwirtschaft frühzeitig zu erkennen und gezielt nachhaltige Maßnahmen zu ergreifen. Die entwickelte Methodik bildet somit eine Grundlage für die Integration kreislaufwirtschaftlicher Prinzipien in den Entwicklungsprozess. Insbesondere im Kontext moderner Anforderungen des Mobility Management zeigt sich ihr Potenzial, nachhaltige Innovationen gezielt zu fördern und die Umsetzung der Kreislaufwirtschaft in der industriellen Praxis zu erleichtern.

Modellgestützte Optimierung eines Ultraschall-Torsionsschweißsystems - Dohmen, Markus Daniel; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias; Sextro, Walter
Das Ultraschallschweißen ist in der Verpackungs-, Halbleiter- und Automobilindustrie weit verbreitet. Neben dem Schweißen von Blechen bietet es die Möglichkeit, Folien oder Hülsen zu verschweißen. Konventionelle Schweißsysteme arbeiten mit Längs- oder Biegeschwingungen, deren Hauptanteil in der Schweißebene liegt. Der orthogonale Anteil verursacht zusätzliche Belastungen im Schweißgut. Bei der Verwendung von Torsionsschwingungen wird die orthogonale Komponente der Schwingung nahezu eliminiert. In diesem Beitrag wird ein System vorgestellt, bei dem die Torsionsschwingung durch tangentiale Polarisation der Piezokeramiken erzeugt wird. Der Transducer ist axial oberhalb des Schweißpunktes platziert, sodass die Normalkraft momentfrei aufgebracht wird. Das Schweißwerkzeug weicht beim Schweißvorgang daher seitlich nicht aus. Zudem wird das Schweißen an schwer zugänglichen Positionen vereinfacht, da der Systemaufbau deutlich schlanker ist als konventionelle Ultraschallschweißsysteme. Die Auslegung des Torsionsschwingsystems stellt eine Herausforderung dar. Insbesondere muss die Lagerung des Schwingers betrachtet werden, da diese die Normalkraft übertragen und zugleich die Schwingung nicht beeinträchtigen soll. Der Schweißprozess bewirkt eine Verschiebung von Schwingungsknoten und Resonanzfrequenzen. Im Rahmen des Vortrags wird ein Finite-Elemente-Simulationsmodell vorgestellt, das in Kombination mit einem Lastmodell das Systemverhalten während des Schweißprozesses abbildet. Die Geometrie des Transducers wurde schrittweise so angepasst, dass die Schwingamplitude im Lagerungspunkt minimiert wird.

Overcoming Digital Inequalities—Identification and Characterisation of Digitally Resilient Schools in Different Countries Using ICILS 2023 Data - Niemann, Jan; Eickelmann, Birgit; Drossel, Kerstin (Education Sciences)
(1) Background: As digitalisation transforms society, digital competences are increasingly essential. Yet students’ digital competences often vary significantly, largely influenced by socio-economic background. Some schools—termed “resilient schools”—effectively counter these disadvantages and foster high digital competence. This study investigates the prevalence of such schools and examines how they differ from others. (2) Methods: Drawing on representative ICILS 2023 data, quantitative secondary analyses—including descriptive statistics, t-tests, and multiple regression—were conducted. Following the identification of resilient schools, in-depth analyses focus on those countries with substantial proportions of resilient schools above 10 percent (Austria, Italy, and Portugal), as these countries seem to have effective strategies to foster school resilience. (3) Results: The findings highlight considerable cross-national variation, indicating that school resilience is context-dependent. Resilient schools consistently emphasise student learning-related factors—such as ICT-related attitudes and educational aspirations—while the influence of home environments is less pronounced than in other schools. (4) Conclusions: Strengthening student learning-related factors appears to be crucial for building digital resilience. These insights can inform policy and practice aimed at fostering educational equity and closing the digital divide, particularly in socio-economically disadvantaged contexts.